Analisis Pola Makan, Asupan dan Status Gizi Mahasiswa Universitas Bina Mandiri Gorontalo pada Masa Pandemi - Fitriani Rahmatismi Blogkod; Arpin (UNIVERSITAS NGUDI WALUYO, 2022)
Nutrition cannot be separated from food because every food we consume containing essential nutrients (macro and micronutrients) which are needed to maintain a healthy body. Adequate nutritional intake can maintain and improve body health and even reduce the risk of diseases, especially during this pandemic. Nutritional status is said to be good if our diet is balanced and followed by the needs of the body. The aims of this study are to analyze the diet, the intake, and the nutritional status of students at the University of Bina Mandiri Gorontalo during the pandemic. This research is a descriptive-analytic study with a cross-sectional design. The subjects of this study were 60 students of Bina Mandiri University Gorontalo who were randomly selected. The subjects were analyzed for diet and nutritional adequacy using a 24-hour food recall questionnaire, NutriSurvey software, the Food Frequency Questionnaire (FFQ) form, and the calculation of nutritional status based on body mass index (BMI). The results of this study showed that students' diets have different frequencies and variation. It is shown that students who still do not meet their energy needs for the energy adequacy as many as 53.3%, for the protein intake as many as 41.7% of students whose protein intake exceeds their needs, for the fat intake and carbohydrates, respectively 56.7% and 48.3% of students whose needs for fat and carbohydrates are still lacking and not according to the RDA standard. As for the nutritional status, students who have normal nutritional status are 58%, Underweight (thin) 34%, and Overweight (Fat) 8%. The diet of students during this pandemic has a different frequency and variety of food, some students are still not sufficient to meet their needs for the energy and macronutrient intake, and most of the students has normal nutritional status. ABSTRAKGizi tidak dapat dipisahkan dari makanan karena setiap makanan yang kita konsumsi mengandung zat gizi esensial yang sangat dibutuhkan untuk menjaga kesehatan tubuh. Asupan gizi yang cukup mampu memelihara dan meningkatkan kesehatan tubuh bahkan mampu menurukan risiko terhadap penyakit terutama dimasa pandemic ini. Status gizi dikatakan baik bila pola makan kita seimbang dan sesuai dengan kebutuhan tubuh. Penelitian in bertujuan untuk menganalisis pola makan, asupan dan satus gizi mahasiswa Universitas Bina Mandiri Gorontalo pada masa pandemi. Penelitian ini adalah penelitian analitik deskriprif dengan desain Cross Sectional. Subjek penelitian ini adalah mahasiswa Universitas Bina Mandiri Gorontalo sejumlah 60 orang yang dipilih secara acak. Pada subjek dilakukan analisis pola makan dan kecukupan gizi mengunakan kuisioner 24-hour food recall dan software NutriSurvey, Formulir Food Frequency Questionnaire (FFQ), serta perhitungan status gizi berdasarkan indeks masa tubuh (IMT). Hasil penelitian menunjukan bahwa pola makan mahasiswa memiliki frekuensi dan variasi yang berbeda-beda, untuk kecukupan energi sebanyak 53,3% mahasiswa yang masih kurang memenuhi kebutuhan energi, untuk asupan protein sebanyak 41,7% mahasiswa yang asupan proteinnya melebihi kebutuhan, untuk asupan lemak dan karbohidrat masing-masing 56,7% dan 48,3% mahasiswa yang kebutuhan lemak dan karbohidratnya masih kurang dan belum sesuai dengan standar AKG. Sementara untuk status gizi, mahasiswa yang memiliki status gizi normal 58%, Underweight (kurus) 34% dan Overweight (Gemuk) 8%. Pola makan mahasiswa pada masa pandemi ini memiliki frekuensi dan variasi makanan yang berbeda, sementara untuk asupan energi dan zat gizi makro sebagian mahasiswa masih belum sesuai mencukupi kebutuhan, dan untuk status gizi sebagian besar mahasiswa dengan status gizi normal